Acupotomy and Thread-embedding Acupuncture Combined with Korean Medicine Treatments for Adhesive Capsulitis of the Hip: A Case Report and Literature Review - Seungeun Lee; Jaeho Song; Jinkyung Park; Chan-Ju Im; Jung-Hyun Kim; Bonhyuk Goo; Yeon-Cheol Park; Yong-Hyeon Baek; Sang-Soo Nam; Byung-Kwan Seo (Journal of Acupuncture Research)
This report presents a case of adhesive capsulitis of the hip (ACH) diagnosed by magnetic resonance imaging in a 37-year-old female whose primary complaint was right hip pain. She underwent Korean medicine (KM) treatments, including acupuncture, pharmacoacupuncture, moxibustion, physiotherapy, and herbal medicine, from July 30, 2023, to September 25, 2023. On August 30, 2023, acupotomy and thread-embedding acupuncture were also initiated. Considerable improvements in hip pain severity were observed, with the Numerical Rating Scale for pain decreasing from six to two. Moreover, the patient also showed improvement in the scores for physical functioning and bodily pain domains of the 36-Item Short Form Survey. Our study results suggest that KM treatments, particularly acupotomy and thread-embedding acupuncture, may be effective for treating ACH. However, further clinical studies are still needed to evaluate the effectiveness of each KM treatment and to explore the long-term outcomes of KM treatments for ACH.